Construction and deconstruction of 'family' by the 'bedroom tax'. Issue 4 (December 2016) - Greenstein, Anat; Burman, Erica; Kalambouka, Afroditi; Sapin, Kate
Abstract This article explores how the Removal of the Spare Room Subsidy policy, commonly known as the Bedroom Tax, works materially and discursively to create certain types of individuals and families as valued and deserving, while portraying others as excessive, wasteful or discretionary. The paper draws on a qualitative study project (Bragget al ., 2015) which generated accounts from 14 families impacted by the policy, as well as 39 interviews with key workers in local schools, charities and community organisations. Through analysis of official texts (such as the policy text and related debates in Parliament) and interview data, the paper explores how particular gendered understandings of care and kinship are constructed, regulated, penalised, and performed via the Bedroom Tax, and how these impact on the everyday lives of families subject to the subsidy removal, and beyond this also to their neighbours and neighbourhoods.